3 - Some Dilemmas of HIV/AIDS Prevention and Coping in a Zambia Village - C. Bawa Yamba, (African Sociological Review, 2004)
The paper examines the activities of researchers in a multidisciplinary HIV/AIDS prevention project in an African rural setting. Like most such projects on health promotion, it entailed trying to pass on superior knowledge on how to save people from dying of AIDS. It draws on an ethnography that spans over a decade of HIV/AIDS prevention in Zambia to show some of the problems inherent in applied projects that do not problematise the very idea of capacity building that aims to empower local people to deal with their own problems. It is argued that such researchers ought to reflect on questions such as what it entails to say that people cope(or are coping) with a given situation of stress and uncertainty; whether this means that such people draw from a range of resources to counter the impact of the situation, or simply drift along with the inevitable and are, thus, able to reduce the impact; and what kind of knowledge isinternaliseable so as to make its recipients think it prudent to act in accordance with its precepts. It is argued social scientists working with HIV/AIDS prevention ought to examine these kinds of underlying assumptions in their work, otherwise they end up creating increased uncertainty and leaving they people they study more vulnerable than before. Examples from the project are drawn to illustrate these issues, to conclude with some tentative points on why it is necessary to be modest about knowing what is best for others, particularly in HIV/AIDS prevention.